A comprehensive application: Molecular docking and network pharmacology for the prediction of bioactive constituents and elucidation of mechanisms of action in component-based Chinese medicine. (February 2021) - Jiao, Xinyi; Jin, Xin; Ma, Yuanyuan; Yang, Yang; Li, Jinjing; Liang, Liuyi; Liu, Rui; Li, Zheng
Graphical abstract: Highlights: The combining of molecular docking and network pharmacology provides a way for the study of traditional Chinese medicine. Based on the theory of TCM, component-based Chinese medicine is the relatively explicit compatibility of active materials. The reliability of the results of these two techniques deserves further experimental investigation. Abstract: Traditional Chinese medicine (TCM) has been used for more than 2000 years in China. TCM has received wide attention recently due to its unique charm. At the same time, its main obstacles have attracted wide attention, including vagueness of drug composition and treatment mechanism. With the development of virtual screening technology, more and more Chinese medicine compounds have been studied to discover the potential active components and mechanisms of action. Molecular docking is a computer technology based on structural design. Network pharmacology establishes powerful and comprehensive databases to understand the relationship between TCM and disease network. In this review, emergent uses and applications of two techniques and further superiorities of the two techniques when embarked to boil down into a tidy system were illustrated. A combination of the two provides a theoretical basis and technical support for the construction of modern TCM based on the compatibility of components and accelerates the realization of two basic elements as well, including the clearness of the pharmacodynamic substances and explanation of the effect of TCM.